Heat Stress and Hormetin-Induced Hormesis in Human Cells: Effects on Aging, Wound Healing, Angiogenesis, and Differentiation - Suresh I. S. Rattan; Ricardo A. Fernandes; Dino Demirovic; Barbara Dymek; Cristovao F. Lima (SAGE Publishing, 2009)
Accumulation of molecular damage and increased molecular heterogeneity are hallmarks of cellular aging. Mild stress-induced hormesis can be an effective way for reducing the accumulation of molecular damage, and thus slowing down aging from within. We have shown that repeated mild heat stress (RMHS) has anti-aging effects on growth and various other cellular and biochemical characteristics of normal human skin fibroblasts and keratinocytes undergoing aging in vitro . RMHS given to human cells increased the basal levels of various chaperones, reduced the accumulation of damaged proteins, stimulated proteasomal activities, increased the cellular resistance to other stresses, enhanced the levels of various antioxidant enzymes, enhanced the activity and amounts of sodium-potassium pump, and increased the phosphorylation-mediated activities of various stress kinases. We have now observed novel hormetic effects of mild heat stress on improving the wound healing capacity of skin fibroblasts and on enhancing the angiogenic ability of endothelial cells. We have also tested potential hormetins, such as curcumin and rosmarinic acid in bringing about their beneficial effects in human cells by inducing stress response pathways involving heat shock proteins and heme-oxygenase HO-1. These data further support the view that mild stress-induced hormesis can be applied for the modulation, intervention and prevention of aging and age-related impairments.